TREN PENGUNGKAPAN INTELLECTUAL CAPITAL INDUSTRI PERBANKAN: SEBUAH BUKTI EMPIRIS DI INDONESIA - Erlin Melani; Endah Suwarni (Jurnal Keuangan dan Perbankan, 2013)
The purposes of this research were to analyze the intellectual capital disclosures volume of banking industriesin Indonesia and to provide additional empirical evidence of variations in IC disclosure that included internalcapital, external capital and human capital in the banking companies in Indonesia. This research used trendleast square method to analyze intellectual capital disclosure trends. Furthermore, One Way Anova test wasused to determine if there was difference in the volume of internal capital disclosure, external capital andhuman capital. The result of this study showed that there was an increase in intellectual capital disclosuretrends, although not as a whole. One of the total sample showed the decrease in intellectual capital disclosuretrend. There was no difference in the volume of disclosure of the three categories in intellectual capital. This wasbecause the IC was still a voluntary disclosure and there were government regulations that indirectly encouragedcompanies to disclose IC such as taxation and labor laws.